Analisis Pola Asuh Orang Tua Pada Kecerdasan Emosional Anak Kelas V MI Nurul Ulum Grabagan - Hardandy, Ammalia Nur Medina Putri; Mahmudiyah, Manzilatul; Fitriana, Ani Qotus Zuhro’ (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This study focused on the emotional intelligence of children coming from parenting. The background of this study is that different parenting styles will cause the emotional intelligence of each child to be different. This study aims to determine whether parenting has an effect on children's emotional intelligence in MI Nurul Ulum Grabagan, and to find out efforts to improve parenting in building children's emotional intelligence in MI Nurul Ulum Grabagan. In this research we used qualitative research methods and used a case study approach. To achieve this goal, researchers use data collection techniques by observation and interviews. The results of the study found that many parenting styles use democratic (authoritative) parenting, but there are also those who use authoritarian parenting. As well as efforts to improve parenting in improving children's emotional intelligence which will later be useful for the future children in social life.